2018
DOI: 10.3390/ijerph15102267
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving, Employment and Social Isolation: Challenges for Rural Carers in Australia

Abstract: Australia has one of the world’s highest life expectancy rates, and there is a rapidly growing need for informal caregivers to support individuals who are ageing, have chronic illness or a lifelong disability. These informal carers themselves face numerous physical and psychological stressors in attempting to balance the provision of care with their personal life, their work commitments and family responsibilities. However, little is known about the specific challenges facing rural carers and the barriers that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 44 publications
1
36
0
Order By: Relevance
“…It is recognised that overall informal cares suffer from worse health outcomes compared to non-cares [1][2][3]; this study investigated an important question that if these disparities could be moderated through carers' social capital. For example, the study investigated if the nature of the local community and community social capital experienced at the personal level moderated carer's health.…”
Section: Research Question and Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…It is recognised that overall informal cares suffer from worse health outcomes compared to non-cares [1][2][3]; this study investigated an important question that if these disparities could be moderated through carers' social capital. For example, the study investigated if the nature of the local community and community social capital experienced at the personal level moderated carer's health.…”
Section: Research Question and Hypothesismentioning
confidence: 99%
“…The health and wellbeing of carers are considered as important as, and are essential to, the health and wellbeing of their care recipients. Yet, informal carers suffer from worse general and mental health outcomes than non-carers [1][2][3] Informal carers play a main role in providing care for someone, closely related to them, a friend or a neighbour, primarily in the home environment with a range of physical, mental and end-of-life health conditions, and disability [4]. They make a significant contribution to the care and wellbeing of people with a disability, mental illness, chronic condition, terminal illness and the elderly [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carers in regional settings are more likely to face barriers with accessing support stemming from transport difficulties. 23 In addition, given the small size of rural communities, confidentiality issues may arise when carers share details of their lives with others living in their local community. Similar to other studies undertaken in rural and regional settings, it was evident carers in our study received significant benefit from peers and personal relationships, which provided significant social capital and enhanced their capacity to continue caregiving.…”
Section: Discussionmentioning
confidence: 99%
“…Some Australian studies have found an additional burden on informal carers in rural areas because of inaccessibility of services and absence of social support services 2 3 . A recent study found that marginalisation of informal carers in rural areas further exacerbates the impact of caregiving on their health 2 . These researchers found that caregiving can have cascading negative health effects when combined with reduced social interactions and geographical isolation as in rural and remote areas 2 12 .…”
Section: Introductionmentioning
confidence: 99%